Social dominance, scent marking, and home range quality in the American marten (Martes Americana) - Herzog, Karen Michelle (University of Guelph, 2003)
In territorial species that use large home ranges, scent cues may function to signal motivation to defend territories. I hypothesized that social dominance was communicated in American marten through anal scent cues and that dominant individuals occupied areas with higher resource levels. I used a captive marten's responses to anal scent to determine a dominance hierarchy for the scent donors. Home ranges were determined through radio-telemetry. Resource levels were sampled and mean resource value was determined for marten home ranges. Results indicated that home range habitat structure correlated with dominance ranking, and that adults and residents had higher dominance rankings than did juveniles and transients. However, high variability between trials of the same stimuli suggested that signals indicating dominance may be weak within a single sample of scent. More work needs to be done on this system to more fully understand the relationship between dominance status and home range quality.